Total electron ionization cross-sections for neutral molecules relevant to astrochemistry - Heathcote, D; Vallance, C (IOP Publishing, 2018)
The binary-encounter Bethe model developed by Kim and Rudd (1994 Phys. Rev. A 50 3954–67), Hwang et al (1996 J. Chem. Phys. 104 2956–66) has previously been used successfully to predict total electron ionisation cross-sections for a wide variety of molecules. Here, we present total electron ionisation cross-sections calculated using the binary-encounter-Bethe model for a range of neutral molecules found in the interstellar medium, planetary and cometary atmospheres, and circumstellar shells. Many of these cross-sections are not amenable to experimental measurement due to the fact that the molecules of interest are highly chemically unstable under terrestrial conditions.